2010
DOI: 10.3109/02703181.2010.538491
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Mortality With the ADL-Staircase in Frail Elderly

Abstract: Objectives: To investigate the ability of the ADL-staircase to predict mortality among older people receiving long-term formal health care and service. Method: This study comprises 626 respondents. Data were collected for 2 cohorts. Results: Crude mortality rate ranged between 9% and 23%. Higher scores on the ADL-staircase significantly increased the risk of mortality (RR = 1.253). For the total sample, Youden's index suggested a cutoff value of 6 for mortality on the ADL-staircase. A cutoff value of 4 was sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…The ADL staircase is administrated using a combination of interview and observation. The validity and reliability of the ADL staircase is good for the age group in present study [17,18] and has recently been found to predict mortality [19]. The number of activities managed independently (0–9) was summarized at baseline and at each follow-up.…”
Section: Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…The ADL staircase is administrated using a combination of interview and observation. The validity and reliability of the ADL staircase is good for the age group in present study [17,18] and has recently been found to predict mortality [19]. The number of activities managed independently (0–9) was summarized at baseline and at each follow-up.…”
Section: Methodsmentioning
confidence: 83%
“…Developing a higher degree of ADL dependence according to the ADL staircase has been found to indicate increased risk of dying [19]. For the older person (80+), being independent means a lot for self-confidence and feelings of pride and satisfaction [2].…”
Section: Discussionmentioning
confidence: 99%
“…Depression has been shown as a risk factor for developing ADL-dependency in previously independent subjects (Mehta et al, 2002). Therefore, we hypothesize that even slight ADL-dependency in octogenarians could have an explanatory role of mortality in depressed individuals (Mill an-Calenti, et al, 2010;Jakobsson & Karlsson, 2011. We suggest that future research should focus on clarifying the causal and temporal relationship between depressive symptoms and the development of ADL-dependency.…”
Section: Discussionmentioning
confidence: 93%
“…Para idosos com potencial de marcha, os testes de velocidade de marcha estão amplamente estudados e demonstram estar associados à fragilidade funcional do idoso [36]. Frequentemente, em estudos relacionados com a identificação de estados frágeis na pessoa idosa, são identificados os domínios da mobilidade, da independência em AVD e nos autocuidados, como significativos indicadores de fragilidade [37][38][39]. Os resultados do presente estudo parecem assim indicar estarem relacionados com os perfis de fragilidade dos idosos, pelo que futuros estudos sobre a Velocidade do Alcance em Tarefas de Atenção e em Tarefas de Memória devem procurar relacionar os seus valores com Índices de Fragilidade.…”
Section: Discussionunclassified